Minimizing blind men effect in strategic group research: Visualizing complex turbulent markets1. (25th April 2019) - Rebière, Philippe; Mavoori, Hareesh
Abstract: Increasing complexity and turbulence of modern markets calls for nonstatic multitheoretical/empirical approaches with intrinsic triangulation and intuitive strategic cluster visualization to minimize the "blind men effect" to offer unbiased insights for various stakeholders: corporate strategic managers, policy researchers, and market legislators. This study presents a refined framework for multi‐time‐point dynamic analysis that integrates and superposes multiple dimensions of strategic flexibility, agility, and orientation for cross‐validated insights. It also addresses long‐standing critical debates on strategic group theory via the metaphor of the blind men and the elephant justifying the need for an in‐depth, multiperspective approach. Our approach reveals the evolution of the market structure (strategic and competitive dynamics) of the French pharmaceutical market over time by mapping and interpreting strategic movements over a turbulent time period.